Thromboelastometry-guided intraoperative haemostatic management reduces bleeding and red cell transfusion after paediatric cardiac surgery. (10th October 2014) - Nakayama, Y.; Nakajima, Y.; Tanaka, K. A.; Sessler, D. I.; Maeda, S.; Iida, J.; Ogawa, S.; Mizobe, T.
Abstract : Background: Thromboelastometric evaluation of coagulation might be useful for prediction and management of bleeding after paediatric cardiac surgery. We tested the hypothesis that the use of a thromboelastometry-guided algorithm for blood product management reduces blood loss and transfusion requirements. Methods: We studied 78 patients undergoing paediatric cardiac surgery with cardiopulmonary bypass (CPB) for the initial 12 h after operation. Stepwise multiple linear regression was used to develop an algorithm to guide blood product transfusions. Thereafter, we randomly assigned 100 patients to conventional or algorithm-guided blood product management, and assessed bleeding and red cell transfusion requirements. Results: CPB time, post-bypass rotational thromboelastometry (ROTEM ® ) EXTEM amplitude at 10 min (A10), and FIBTEM-A10 were independently associated with chest tube drainage volume during the initial 12 h after operation. Discriminative analysis determined cut-off values of 30 mm for EXTEM-A10 and 5 mm for FIBTEM-A10, and estimated optimal intraoperative fresh-frozen plasma and platelet concentrate transfusion volumes. Thromboelastometry-guided post-bypass blood product management significantly reduced postoperative bleeding (9 vs 16 ml kg −1, P <0.001) and packed red cell transfusion requirement (11 vs 23 ml kg −1, P =0.005) at 12 h after surgery, and duration of critical care stay (60 vs 71 h, P =0.014). Conclusions: Rotational thromboelastometry-guided early haemostatic intervention by rapid intraoperative correction of EXTEM-A10 and FIBTEM-A10 reduced blood loss and red cell transfusion requirements after CPB, and reduced critical care duration in paediatric cardiac surgical patients. Clinical trial registration: UMIN Clinical Trials Registry UMIN000006832 (December 4, 2011).